Urgency of Corporate Social Responsibility (CSR) for Corporate Advancement in Indonesia - Seran, Maria Dinda Ayu Rosari Luruk; Hwihanus, Hwihanus; Lavenia, Lisa (LPPM Universitas Jambi, 2024)
This study examines the urgency of Corporate Social Responsibility (CSR) for corporate advancement in Indonesia, highlighting the critical role of CSR in fostering sustainable business practices and enhancing stakeholder relationships. Utilizing a literature review methodology, the research compiles and analyzes data from various sources, including academic journals, books, and articles, to explore the trends, implementations, and impacts of CSR initiatives. The findings reveal that companies integrating CSR into their core strategies not only improve their reputations and stakeholder engagement but also contribute to long-term economic development and environmental sustainability. Discussion points emphasize the importance of transparency and accountability in CSR practices, which are crucial for gaining consumer trust and achieving regulatory compliance. The study concludes that adopting comprehensive CSR strategies is imperative for Indonesian companies to ensure their sustainable growth and to positively impact the broader community and environment, underscoring the necessity for continued focus and improvement in CSR practices. Keyword: Corporate Social Responsibility (CSR), Corporate Advancement, Sustainable Business Practices, Stakeholder Relationships, Environmental Sustainability